INTEGRATION OF JUMIANG BEACH IN INTERACTIVE TEACHING MATERIALS OF DESCRIPTION TEXT AS STUDENT’S CHARACTER STHRENGTHENING EFFORT - Ayyu Subhi Farahiba; Albitar Septian Syarifudin (IKIP Siliwangi, 2023)
Based on the results of the needs analysis, the learning resources used by teachers are still limited. Teachers need to develop innovative and contextual teaching materials so that students can better understand them. Regional marine tourism can be used as a learning resource, especially in descriptive text material. This study aims to describe the integration of Jumiang Beach marine tourism as a descriptive text teaching material. This research uses descriptive qualitative method. In this research, the object of research is the seventh grade students of SMP Tsamrotul Ulum. Data was collected through interviews, observation, and documentation. Interviews were conducted with Indonesian language teachers and seventh grade students. Observations were made by visiting the Jumiang Beach tourist attraction as material for making learning videos. The results of the analysis show that Jumiang Beach tourism objects are very relevant and useful to use as descriptive text teaching materials because the objects described are close to students, add insight and knowledge, students understand the material better because they seem to see objects directly through learning videos in teaching materials, and students feel interested and happy because they learn through interactive teaching materials so that learning becomes more meaningful. It can be concluded that Jumiang Beach which is integrated in interactive descriptive text teaching materials gets very good and positive responses from teachers and students. Keywords: Tourism; Jumiang Beach; Interactive Teaching Materials